Effect of Crocus sativus L. stigma (saffron) against subacute effect of diazinon: histopathological, hematological, biochemical and genotoxicity evaluations in rats - Alireza Timcheh Hariri; Seyed Adel Moallem; Mahmoud Mahmoudi; Bahram Memar; Bibi Marjan Razavi; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2018)
Objective: In this study, the effects of saffron stigma against subacute diazinon (DZN) toxicity on enzymes levels, biochemical, hematological, histopathological and genotoxicity indices were studied in rats. Methods: Vitamin E (200 IU/kg) and the aqueous extract of saffron (50, 100 and 200 mg/kg) were injected intraperitoneally three times per week alone or with DZN (20 mg/kg/day, orally) for 4 weeks. The hematological and biochemical parameters were evaluated at the end of 4 weeks. Results: Reticulocytes counts, alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), creatine phosphokinase, CPK-MB, gama glutamyl transferase (GGT), uric acid and micronucleus indices were increased significantly but total protein and RBC cholinesterase activity were decreased in the DZN-treated group. Saffron prevented the effect of DZN on GGT (50 mg/kg), LDH, CPK and CPK-MB (100 and 200 mg/kg) levels. An increased uric acid and reduced protein levels by DZN were prevented by vitamin E and some doses of saffron. A significant reduction was observed in platelets, RBC, hemoglobin and hematocrit indices in the DZN group. Saffron and vitamin E prevented this reduction. Vitamin E and saffron did not reduce the effect of DZN on RBC cholinesterase activity. The extract and vitamin E could not prevent DZN genotoxicity in the micronucleus assay. Other biochemical parameters and pathological evaluation did not show any abnormality in tissues of all groups. Conclusion: This study shows that vitamin E and saffron reduce DZN induced hematological and biochemical toxicity. However, they do not prevent the genotoxicity induced by DZN.